HYPOTHETICAL PROTEINS OF MYCOBACTERIUM TUBERCULOSIS H37Rv AS DRUG TARGETS - ZAHRA M. AL-KHAFAJI (International Journal of Pharma and Bio Sciences, 2014)
Hypothetical proteins often with unknown functions . Mycobacterium tuberculosis H37Rv has a very large number of such proteins , which can be exploited as drug target as the bacterium became more virulent with developing antibiotic resistance to first line and second line of drugs . Some hypothetical proteins (290 proteins) were studied from different aspects related to find the druggable proteins . Results shown that some of it get good druggability score such as Rv2074, Rv2827c , Rv0295c which are worth to be subjected to further scheme of drug design such as docking or using other computational techniques .